Monitoring Use of Antibiotic with ATC/DDD and DU 90% on Pediatric Patients at One of the Government Hospitals in East Borneo - Risna Agustina; Wisnu Cahyo Prabowo (Journal of Tropical Pharmacy and Chemistry, 2020)
Pediatric patients are among the recipients of most antibiotic treatment in hospitals so as to induce irrational use of antibiotics. This study aims to monitor the use of antibiotics in pediatric using ATC/DDD methods and DU 90%. This study is a descriptive study with a retrospective study by taking data from medical records to assess the use of antibiotics in pediatric patients with various diseases in the hospital. Quantitative data analysis using ATC/DDD methods showed that the widely used antibiotic was ceftriaxone 16,93% DDD. Antibiotics that include into the DU segment 90% use in the order of the largest to the smallest, respectively are ceftriaxone, metronidazole, cefotaxime, gentamycin, polymyxin B, colistin, cotrimoxazole, cefuroxime, and meropenem. The prescribing effect of short-term antibiotic use in basic medical services may increase the incidence of resistance.